Regional MRI Perfusion Measures Predict Motor/Executive Function in Patients with Clinically Isolated Syndrome. (23rd January 2014) - Papadaki, Efrosini Z.; Simos, Panagiotis G.; Mastorodemos, Vasileios C.; Panou, Theodora; Maris, Thomas G.; Karantanas, Apostolos H.; Plaitakis, Andreas
Abstract : Background . Patients with clinically isolated syndrome (CIS) demonstrate brain hemodynamic changes and also suffer from difficulties in processing speed, memory, and executive functions. Objective . To explore whether brain hemodynamic disturbances in CIS patients correlate with executive functions. Methods . Thirty CIS patients and forty-three healthy subjects, matched for age, gender, education level, and FSIQ, were administered tests of visuomotor learning and set shifting ability. Cerebral blood volume (CBV), cerebral blood flow (CBF), and mean transit time (MTT) values were estimated in normal-appearing white matter (NAWM) and normal-appearing deep gray Matter (NADGM) structures, using a perfusion MRI technique. Results . CIS patients showed significantly elevated reaction time (RT) on both tasks, while their CBV and MTT values were globally increased, probably due to inflammatory vasodilation. Significantly, positive correlation coefficients were found between error rates on the inhibition condition of the visuomotor learning task and CBV values in occipital, periventricular NAWM and both thalami. On the set shifting condition of the respective task significant, positive associations were found between error rates and CBV values in the semioval center and periventricular NAWM bilaterally. Conclusion . Impaired executive function in CIS patients correlated positively with elevated regional CBV values thought to reflect inflammatory processes.